ANALYSIS OF FACTORS AFFECTING THE DEMAND FOR SOYBEAN IN NORTH SUMATRA PROVINCE - Isqi Mayani Sagala; Suryadi Suryadi; Adhiana Adhiana (Jurnal Mahasiswa Agribisnis, 2022)
A soybean is a food crops and vegetable proteins source important for people in North Sumatra Province. A soybean demands increased from year to year in North Sumatra Province but A soybean production decreased from year to year in North Sumatra Province. It caused by several factors such as a population growth, percapita income, and change in food consumption patterns with economic growth in North Sumatra Province. Therefore, the purpose of this study is to analyze a factor that influences soybean demand in North Sumatra Province. The data used a secondary data sourced in the form of time series from 2005 -2015. The analysis model is a double linear regression The partial t-test result showed that the of corn price, total population, percapita income and amount of industry for consumption has a significant influence on soybean demand in North Sumatra Province. While soybean price and amount of industry for feed influence not significant to soybean demand in North Sumatra Province. Price elasticity value smaller than one hence elasticity has inelastic. Cross elasticity of corn price has negative and it is complementary goods for soybean. Percapita income elasticity value is positive sign hence this thing indicates that soybean normal goods.